Analysis of Literature Teachers’ Roles within Online Environments Case Study: English Literature Teachers, Laghouat University - Medjelled, Meriem; Teggari, Soumia; Gasmi,Mustapha (University of Ammar Theledji -Laghouat, 2021)
The purpose of this study is to examine the university literature teachers’ roles in online learning environments, an empirical work is conducted using a multi-method approach to triangulate and contextualize the findings and enrich the understanding of the literature teachers' roles in this networked learning community (NLC). In the study, a targeted sample of 9 teachers of literature from the department of English at Ammar Thelidji University in Laghouat, Algeria, were surveyed about their roles as online educators in the field of literature, focusing on the changes observed compared to teaching in a traditional setting. The data, on the other hand, was collected through an online questionnaire administrated to the targeted sample; it was then analyzed using a descriptive-analytical approach for an in-depth description and analysis of the selected variables. The main findings of this study revealed that literature teachers’ roles within online education were likely to alter compared to conventional teaching. Hence, teachers decided to combine both teaching methods for a better outcome, since online education alone is insufficient for teaching a subject like literature